Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1158/0008-5472.can-18-0173
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtype-Specific Immunocompetent Models of High-Grade Urothelial Carcinoma Reveal Differential Neoantigen Expression and Response to Immunotherapy

Abstract: High-grade urothelial cancer contains intrinsic molecular subtypes that exhibit differences in underlying tumor biology and can be divided into luminal-like and basal-like subtypes. We describe here the first subtype-specific murine models of bladder cancer and show that Upk3a-Cre; Trp53; Pten; Rosa26 (UPPL, luminal-like) and BBN (basal-like) tumors are more faithful to human bladder cancer than the widely used MB49 cells. Following engraftment into immunocompetent C57BL/6 mice, BBN tumors were more responsive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 34 publications
(53 reference statements)
6
103
1
Order By: Relevance
“…Tumors in the MB49 model develop rapidly, however MB49 cell lines vary considerably from lab to lab and in some cases, display a rapid aggressive growth rate that precludes studies of adaptive immunity (El Behi et al, 2013;Saito et al, 2018). In addition, the tumor that develops is homogeneous likely not accurately reflecting human bladder cancers (Saito et al, 2018). The induction of bladder cancer by BBN leads to more heterogeneous tumors, which reflect human disease (Fantini et al, 2018;Sfakianos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Tumors in the MB49 model develop rapidly, however MB49 cell lines vary considerably from lab to lab and in some cases, display a rapid aggressive growth rate that precludes studies of adaptive immunity (El Behi et al, 2013;Saito et al, 2018). In addition, the tumor that develops is homogeneous likely not accurately reflecting human bladder cancers (Saito et al, 2018). The induction of bladder cancer by BBN leads to more heterogeneous tumors, which reflect human disease (Fantini et al, 2018;Sfakianos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study we report here follows the analysis of a cohort of advanced stage MIBC. In this setting, understanding the molecular underpinnings of a sample is critical to better predicting how they will respond to therapy(10), especially ICIs (12,13). To better characterize the spatial arrangement of key molecular characteristics such as tumor-intrinsic subtype, TIL exclusion and composition, and tumor-stroma interaction we leveraged multiple traditional bulk and spatial platforms in conjunction highly multiplexed profiling by GeoMx within FFPE tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although responses can be durable, only 20-30% of patients with MIBC will respond to immune checkpoint inhibitors (ICIs), arguing for the identification of novel drug targets and need for a deeper understanding of predictive biomarkers to enrich for responses to current standard of care therapies (6,7). Multiple studies have identified distinct RNA expression subtypes within MIBC termed "luminal" and "basal-like" (8), each of which has unique gene expression patterns which have important implications for disease management with conventional chemotherapy (9)(10)(11) and immunotherapies (12). Response to immune checkpoint inhibitors in urothelial bladder cancer has been associated with several potential biomarkers including tumor mutation burden, tumor molecular subtype and PD-L1 expression on CD8+ tumor infiltrating lymphocytes (TILs) and other immune cells (7,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Many neoantigen prediction algorithms rely heavily on peptide/MHC binding affinity predictions to rank epitopes (7)(8)(9)(10)(11)(12)(13)(14). Unlike murine preclinical models, where in vivo/ex vivo methods to further screen for immunogenicity can be applied (3,15), no such benchtop prediction method for immunogenicity is currently available for humans. We have previously demonstrated in multiple murine models that the number of predicted neoantigens is much higher than the number of confirmed immunogenic neoantigens (15).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike murine preclinical models, where in vivo/ex vivo methods to further screen for immunogenicity can be applied (3,15), no such benchtop prediction method for immunogenicity is currently available for humans. We have previously demonstrated in multiple murine models that the number of predicted neoantigens is much higher than the number of confirmed immunogenic neoantigens (15). Studies demonstrate that in some tumors, the number of predicted neoantigens is far greater than the number of immunogenic neoantigens that have been identified in mouse models (16,17).…”
Section: Introductionmentioning
confidence: 99%